A change of culture: reducing blood culture contamination rates in an Emergency Department. Issue 1 (6th June 2016) - Bentley, James; Thakore, Shobhan; Muir, L; Baird, Alastair; Lee, Jennifer
Abstract : Blood cultures are an important investigation to help tailor effective management for patients with severe sepsis. Frequent contaminated samples increase laboratory workload and can delay or cause incorrect changes to patient management. This can prolong patient hospitalisation, increase the risk of harm and increase cost to health boards. Current guidelines advocate a contamination rate of 2–3%. From January 2013 to November 2014 inclusive, the contamination rate was 4.74% in our Emergency Department, responsible for initial management and investigation of over 40 cases of sepsis per month. A Quality Improvement team was created to try to reduce contamination rates to the recommended target. An initial baseline survey of local staff showed good understanding of when to obtain a blood culture but there was variability in the methods and equipment used. A project was then conducted which focused on rationalising and standardising equipment and technique for blood culture sampling along with staff education to support this change. A simple department target of 30 days free from a contaminated blood culture was created which, if achieved, would ensure a contamination rate of less than 3%. This was supported by ongoing surveillance of contamination rates and investigation of contaminated sample cases. We were able to then identify high risk patients and factors which increased the chance of blood culture contamination. This allowed us to formulate solutions to help reduce the risks of contamination. Department achievements and learning points to help prevent further contamination were fed back positively to all staff. This project operated for 12-months and successfully reduced local contamination rates to 2.0%.